Penerapan Aplikasi Keuangan Berbasis Android SIAPIK Pada Penyajian Laporan Keuangan Anugrah Markisa - Windi Wardana; Mukhammad Idrus; Samsinar (Asosiasi Dosen Akuntansi Indonesia, 2026)
The purpose of this study is to examine the presentation of Anugrah Markisa's financial statements using the SIAPIK application, an Android-based financial application. The research subjects were the owners of Anugrah Markisa's MSMEs, who aimed to observe Anugrah Markisa's financial transaction records for 30 days. Data collection methods included documentation, observation, and interviews. Qualitative descriptive techniques were used in data analysis. Data collection, data presentation, and conclusion drawing are components of the observation technique. The data used included MSME overviews and related documents. The results of the study indicate that Anugrah Markisa's MSMEs have been greatly assisted and supported in preparing automated and more accurate financial statements since they implemented the SIAPIK application. The outputs from Anugrah Markisa's financial reporting capabilities include income statements, balance sheets, and cash flow statements. Simple bookkeeping in accordance with SAK-EMKM is also part of Anugrah Markisa's MSME capabilities.